The popular scientific book-based coastal gastropod’s diversity as local potential: Practicality and effectiveness on student’s critical thinking ability - Hery Fajeriadi; Muhammad Zaini; D. Dharmono; Bimo Aji Nugroho; F. Fahmi; Antung Fitriani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Developing learning tools based on local potential is necessary because it directly relates to students' daily lives. One of them is a Popular Science Book (PSB), which highlights the potential of gastropods in coastal areas as a subject for observing biodiversity. The implementation of assessments and the value of students' critical thinking abilities still need to be improved. This research aimed to implement the PSB based on its practicality and effectiveness in improving students' critical thinking abilities. The research method used formative evaluation, focused on testing the practicality and efficacy of valid development products. Practicality was analysed based on student response tests through the percentage of responses and the implementation of the learning plan (LP) through categorization. Furthermore, effectiveness was analysed based on student learning outcomes through the percentage of completeness and achievement of critical thinking ability indicators through the N-gain test. The research results prove that the PSB developed was practical and effective. Apperception and interpretation were two of the three stages of implementation of the LP that received the highest average, where students could provide theoretical ideas based on appreciation of environmental issues. This was also supported by the student's critical thinking ability tests, where the interpretation aspect obtained the highest N-gain. The development of local potential-based PSB shows positive impacts, especially ease of use, interest in learning, motivation, apperception, and interpretation. However, it is still necessary to study in more depth the causal factors and solutions for the differences in results between the implementation of the LP at the conclusion stage and the indicators of critical thinking in the inference aspect.